2017
DOI: 10.1001/jama.2017.11137
|View full text |Cite|
|
Sign up to set email alerts
|

Mutation Detection in Patients With Advanced Cancer by Universal Sequencing of Cancer-Related Genes in Tumor and Normal DNA vs Guideline-Based Germline Testing

Abstract: IMPORTANCE Guidelines for cancer genetic testing based on family history may miss clinically actionable genetic changes with established implications for cancer screening or prevention.OBJECTIVE To determine the proportion and potential clinical implications of inherited variants detected using simultaneous sequencing of the tumor and normal tissue ("tumor-normal sequencing") compared with genetic test results based on current guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

26
392
1
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 406 publications
(447 citation statements)
references
References 30 publications
26
392
1
2
Order By: Relevance
“…Although some studies in PDAC cohorts have not analyzed CHEK2, 9,25 the prevalence of germline CHEK2 mutations was approximately 4% (7 of 176) among patients with pancreatic cancer in the study by Mendelker et al 10 Further studies are needed to clarify the risk for PDAC in individuals with germline CHEK2 PGVs. Although some studies in PDAC cohorts have not analyzed CHEK2, 9,25 the prevalence of germline CHEK2 mutations was approximately 4% (7 of 176) among patients with pancreatic cancer in the study by Mendelker et al 10 Further studies are needed to clarify the risk for PDAC in individuals with germline CHEK2 PGVs.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Although some studies in PDAC cohorts have not analyzed CHEK2, 9,25 the prevalence of germline CHEK2 mutations was approximately 4% (7 of 176) among patients with pancreatic cancer in the study by Mendelker et al 10 Further studies are needed to clarify the risk for PDAC in individuals with germline CHEK2 PGVs. Although some studies in PDAC cohorts have not analyzed CHEK2, 9,25 the prevalence of germline CHEK2 mutations was approximately 4% (7 of 176) among patients with pancreatic cancer in the study by Mendelker et al 10 Further studies are needed to clarify the risk for PDAC in individuals with germline CHEK2 PGVs.…”
Section: Discussionmentioning
confidence: 96%
“…10,26,27 If adherence to clinical testing guidelines is a prerequisite for germline testing, patients with PDAC are among those with the highest prevalence of undetected actionable germline mutations. 10,26,27 If adherence to clinical testing guidelines is a prerequisite for germline testing, patients with PDAC are among those with the highest prevalence of undetected actionable germline mutations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lifetime risk of developing breast and ovarian cancer related to this syndrome have been estimated to be approximately 70%–80% and 20%–50%, respectively (Antoniou et al, ; Kuchenbaecker et al, ). On average, pathogenic variants in BRCA1/2 account for approximately 10% of all breast cancer cases (Mandelker et al, ; Mavaddat, Antoniou, Easton, & Garcia‐Closas, ) and 10%–15% of ovarian cancer (Morgan et al, ; Toss et al, ; Vergote et al, ). Among women with a pathogenic variant in BRCA1/2 , risk reducing surgical intervention has been shown to improve cancer‐specific and overall mortality (Finch et al, ; Li et al, ; Rebbeck, Kauff, & Domchek, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, with the hope of precision medicine has come expanding interest in cataloguing both the acquired as well as inherited genetic variants that contribute to diverse cancers occurring across the lifespan. Already, studies examining children with solid tumors and adults with various advanced solid tumors have shown that 8.6% and 14.3%, respectively, have inherited mutations in known cancer susceptibility genes [1, 2]. These data suggest that inherited susceptibility likely contributes to many cancer types, with proportions differing by cell of origin and disease features (eg, 4.6% with localized prostate cancer vs 11.8% with metastatic prostate cancer) [3].…”
Section: Introductionmentioning
confidence: 99%